KEPEMIMPINAN PEREMPUAN DALAM PERSEPEKTIF HUKUM ISLAM (Studi Komparatif antara Pemikiran KH. Husein Muhammad dan Prof. Siti Musdah Mulia) - Samsul Zakaria (Universitas Islam Indonesia, 2013)
This research with literature models and combined with interviews seeks to answer the question, firstly, how the concept of women’s leadership in the perspective of Islamic law. Secondly, a comparative analysis of KH. Husein Muhammad’s thought and Prof. Siti Musdah Mulia’s thought on women’s leadership. The conclusion of this study is that the Islamic law (Shariah) does not provide a practical explanation of a firm and clear on women’s leadership. Technically it is true that Islam does not provide practical guidance but substantively Islam provides breadth for women to play a role in the public sector. This is because men and women are created in the same position and have the same opportunities in areas such as work and career, including to be the leader. KH. Husein Muhammad as the first figure of this study confirms an understanding that women are actually capable of being a leader among men. In line with that the woman has the right to be a leader as owned by men. Meanwhile, Prof. Siti Musdah Mulia as te second figure expressed the same thing that appreciate women’s leadership. More specifically, he describes the unique and different conception about the character of women’s leadership. For him, women who become leaders do not have to change into males assertive and authoritative. Leadership remains ideal when built on a joint gentleness and compassion as the basic nature of women.